Participation of Women in Decision Making in Goat Rearing in Nadia District of West Bengal - Tudu, Nirmal Kumar; Roy, Dulal Chandra (International Journal of Social Sciences and Management, 2015)
The present research work was done in Nadia district in the state of West Bengal during January, 2011 to December, 2013. From the study revealed that women were responsible for the tasks like taking the animals for grazing, fodder collection, chaffing and storage of fodder etc. Almost entire activities, so far as washing and cleaning of goat sheds and feeding of goats, were being performed by the women. Results indicated that the rural women participation in five blocks in breeding activities was found to be minor activities due to social mores and taboos in society. Analysis of the data revealed that women participation in health care activities was found to be minor activities due to lack knowledge regarding health care activities. The women in their late middle and old age actively participated in health care as they had learnt the things by seeing and out of experience. Most of the respondents interviewed were of the view that they require lot of training and knowledge with regard to the health care aspects. From the study it was seen that no women take decision without the permission of their spouse for selling the animals. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12303 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 119-122